Profitability and Leverage, on Firm Value with Good Corporate Governance as Moderation - Dwi Anggraeni; Siti Jolekhah; Tri Neliana (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Study This aim For test influence profitability and leverage against mark company with Good Corporate Governance (GCG) as variable moderation. Population in study This is a manufacturing company subsector food and beverages listed on the Indonesia Stock Exchange (BEI) for the 2019-2022 period. Retrieval technique sample used​ is purposive sampling with The company sample is 29 with 5 years observation, so A total of 116 data samples were obtained. Data sources used in study This namely secondary data. Deep data analysis techniques study This use analysis regression multiple and Moderated Regression Analysis (MRA). Research result show that profitability and leverage matter to the value of the company. Apart from that, Good Corporate Governance proven moderate influence profitability to Company value, however No capable moderate the effect of leverage on mark company.